2011
DOI: 10.1029/2010jb007734
|View full text |Cite
|
Sign up to set email alerts
|

Study of the variation of thermal conductivity with water saturation using nuclear magnetic resonance

Abstract: [1] In this paper, we present a method that allows one to correct thermal conductivity measurements for the effect of water loss when extrapolating laboratory data to in situ conditions. The water loss in shales and unconsolidated rocks is a serious problem that can introduce errors in the characterization of reservoirs. For this study, we measure the thermal conductivity of four sandstones with and without clay minerals according to different water saturation levels using an optical scanner. Thermal conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…There are several models used to calculate the bulk thermal conductivity ( K b ) of porous and variably saturated rocks [ Jorand et al , 2011]. The geometric mean bulk thermal conductivity is applicable only when the constituent conductivities vary by less than one order of magnitude [ Sass et al , 1971] and is applicable mainly in rocks with water saturation >60% [ Jorand et al , 2011]. Neither of these conditions is applicable to our samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several models used to calculate the bulk thermal conductivity ( K b ) of porous and variably saturated rocks [ Jorand et al , 2011]. The geometric mean bulk thermal conductivity is applicable only when the constituent conductivities vary by less than one order of magnitude [ Sass et al , 1971] and is applicable mainly in rocks with water saturation >60% [ Jorand et al , 2011]. Neither of these conditions is applicable to our samples.…”
Section: Methodsmentioning
confidence: 99%
“…The calculated arithmetic mean and harmonic mean bulk thermal conductivities ( K b ) are 1.30 ± 0.21 W·m −1 ·K −1 and 1.24 ± 0.20 W·m −1 ·K −1 , respectively. Following the approach of Jorand et al [2011]we calculate a arithmetic‐harmonic mean of 1.27 ± 0.21 W·m −1 ·K −1 , which is an average of the two means. The cumulative uncertainties were calculated by propagating the errors resulting from averaging matrix thermal conductivity, porosity, and volumetric water saturation.…”
Section: Methodsmentioning
confidence: 99%
“…Where ø is the total porosity (%), and C a constant normally used to adjust NMR logs and traditionally set at 10 in sandstones (Jorand et al, 2011). Assuming that the mobility of reservoir fluids is primarily controlled by pore sizes, a fixed T 2 value can relate directly to a pore size at or below which fluids will not move.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…The Berea sandstone was characterized by a unimodal distribution of T 2 relaxation whereas Donnybrook showed a broader multimodal distribution. In our previous work, large proportions of the pores in these sandstones were demonstrated to be over one micron (Honari et al, 2013) and the relatively small numbers of micro pores observed was attributed to the presence of claybound water (Jorand et al, 2011;Straley et al, 1997). The distributions of T 2 relaxation for the carbonate rocks consisted of two distinct peaks, which was consistent with the pore size distributions previously reported (Bijeljic et al, 2013a;Tanino and Blunt, 2012).…”
Section: Nmr Distributions Of T 2 Relaxation For Sandstones and Carbomentioning
confidence: 99%